Interactional Effects of Climate Change Factors on the Water Status, Photosynthetic Rate, and Metabolic Regulation in Peach - Jiménez, Sergio; Fattahi, Masoud; Bedis, Khaoula; Nasrolahpour-moghadam, Shirin; Irigoyen, Juan José; Gogorcena, Yolanda (Frontiers in Plant Science, 2020)
Environmental stress factors caused by climate change affect plant growth and crop production, and pose a growing threat to sustainable agriculture, especially for tree crops. In this context, we sought to investigate the responses to climate change of two Prunus rootstocks (GF677 and Adesoto) budded with Catherina peach cultivar. Plants were grown in 15 L pots in temperature gradient greenhouses for an 18 day acclimation period after which six treatments were applied: [CO2 levels (400 versus 700 µmol mol-1), temperature (ambient versus ambient + 4ºC), and water availability (well irrigated versus drought)]. After 23 days, the effects of stress were evaluated as changes in physiological and biochemical traits, including expression of relevant genes. Stem water potential decreased under drought stress in GF677 and Adesoto genotypes, however, elevated CO2 and temperature affected plant water content differently in both genotypes. The photosynthetic rate of plants grafted on GF677 increased under high CO2, but decreased under high temperature and drought conditions. The photosynthetic rates of plants grafted onto Adesoto were only affected by drought treatment. Furthermore, in GF677, elevated CO2 alleviated the effect of drought, whereas in Adesoto, the same condition produced acclimation in the photosynthetic rate. Stomatal conductance decreased under high CO2 and drought stress in both genotypes, and the combination of these conditions improved photosynthetic water-use efficiency. Changes in the sugar content in leaves and roots were significantly different under the stress conditions in both rootstocks. Meanwhile, the expression of most of the assessed genes was significantly affected by treatment. Regarding genotypes, GF677 rootstock showed more changes at the molecular and transcriptomic level than did Adesoto rootstock. A coordinated shift was found between the physiological status and the transcriptomic responses. This study revealed adaptive responses to climate change at the physiological, metabolic, and transcriptomic levels in two Prunus rootstocks budded with ‘Catherina’. Overall, these results demonstrate the resilient capacity and plasticity of these contrasting genotypes, which can be further used to combat ongoing climate changes and support sustainable peach production.